IN-SEASON ARCHITECTURAL ADAPTATIONS OF THE BICEPS FEMORIS LONG HEAD IN ELITE AUSTRALIAN FOOTBALLERS. Issue 4 (1st February 2017) - Timmins, Ryan; Bourne, Matthew; Williams, Morgan; Opar, David
Abstract : Background: Hamstring strain injuries (HSI) are the predominant injury in the elite Australian Football League (AFL). Athletes who possess short biceps femoris long head (BFlh) fascicle lengths have an increased risk of future HSI than those who have longer fascicles. Fascicle length can be altered following interventions, however it is unknown what alterations occur in-season. It is also unknown if this may differ between those with and without a history of HSI. Objective: Determine what architectural changes occur during an AFL season. Identify if these changes are different between those with and without a history of HSI. Design: Cross-sectional retrospective injury study. Setting: Elite Australian Football. Participants: Thirty elite AFL players with (n=12) and without (n=18) a unilateral history of HSI. Assessment of Risk Factors: BFlh architecture was assessed once a month on six separate occasions during the 2016 AFL season using two-dimensional ultrasound. Main Outcome Measurements: BFlh fascicle length. Results: Limbs with a history of HSI possess shorter fascicles than previously uninjured limbs at the start and throughout the season. From time point 1 to time point 2, previously injured BFlh fascicle lengths did not significantly change (p=0.247, d= 0.23), whilst the contralateral uninjured BFlh(p=0.009, d =0.56) and athletes with no history of injury (p=0.002, d =0.75), significantly increased BFlh fascicle length. All athletes, independent of injury history, had a significant reduction in fascicle length at time point 6 compared to time point 2. Conclusions: Fascicle lengths of BFlh vary across the in-season period in elite AFL players and the extent of these alterations appears to be influenced somewhat by HSI history. However, independent of injury history, there was a gradual decay in fascicle length as the season progresses.